Effect of silver sulphide (Ag2S) layer towards the performance of copper indium sulphide (CuInS2) quantum dots sensitised solar cell. (12th January 2021) - Mustakim, Nurul Syafiqah; Sepeai, Suhaila; Ludin, Norasikin Ahmad; Teridi, Mohd Asri Mat; Ibrahim, Mohd Adib
The effect of Ag2 S as passivation layer is investigated in the CuInS2 quantum dot sensitised solar cell (QDSSC) application, which is used to improve the photovoltaic performance. In this study, Ag2S layers were deposited by using successive ionic layer adsorption and reaction (SILAR) deposition technique onto prepared TiO2 /CuInS2 QDs thin films. The surface morphology, crystalline structure and optical properties of the samples were carried out using field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM), X-ray diffraction (XRD) and ultra-violet-visible near infrared spectrophotometry (UV-Vis). For electrical properties, Electrochemical Impedance Spectra (EIS), four-point probe and I-V test investigated the interfacial charge-transfer resistances, resistivity and conductivity of the samples. Results showed that the average particle size of the samples increased from 45.61 nm to 74.08 nm after the deposition of Ag2 S layer. The XRD results showed that the crystallite size of TiO2 /CuInS2 /Ag2 S photo anode estimated around 15.32 nm, while UV-Vis analysis indicated that the sample showed better light absorption capability compared to samples without the passivation layers. For electrical properties, TiO2 /CuInS2 /Ag2 S photo anode showed low resistivity values, thus, produced better conductivity of electrons. The performance of the solar cell was found to be improved with the presence of Ag2 S layer with power conversion efficiency of 0.136%. The obtained results showed that TiO2 CuInS2 QDs thin films with Ag2 S passivation layer are applicable as a photo anode in QDSSC applications.